2012
DOI: 10.1038/bjc.2011.594
|View full text |Cite
|
Sign up to set email alerts
|

Randomised phase-II trial of CAPIRI (capecitabine, irinotecan) plus bevacizumab vs FOLFIRI (folinic acid, 5-fluorouracil, irinotecan) plus bevacizumab as first-line treatment of patients with unresectable/metastatic colorectal cancer (mCRC)

Abstract: Background:To compare the efficacy and safety of CAPIRI+bevacizumab (Bev) in comparison with FOLFIRI+Bev as first-line treatment for patients with metastatic colorectal cancer (mCRC).Methods:Patients were randomised to receive either FOLFIRI plus Bev 5 mg kg−1 every 2 weeks (Arm-A) or CAPIRI plus Bev 7.5 mg kg−1 every 3 weeks (Arm-B).Results:Three hundred thirty-three patients (Arm-A=167; Arm-B=166) were enrolled into the study. No difference was observed in median progression-free survival (PFS) (10.0 and 8.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 28 publications
6
16
0
Order By: Relevance
“…It is therefore not surprising that the median survival in the studies included in the present review is lower than that seen in contemporaneous trials. Another possible explanation is the use, in some of the trials, of capecitabine and irinotecan, which, compared with folfir i (leucovorin-5-fluorouracil-irinotecan), have been shown to be associated with inferior survival 18 and toxicity profiles 18,19 . Additionally, the superior pfs seen with first-line combination chemotherapy in the trials included in our systematic review is not maintained over subsequent lines of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that the median survival in the studies included in the present review is lower than that seen in contemporaneous trials. Another possible explanation is the use, in some of the trials, of capecitabine and irinotecan, which, compared with folfir i (leucovorin-5-fluorouracil-irinotecan), have been shown to be associated with inferior survival 18 and toxicity profiles 18,19 . Additionally, the superior pfs seen with first-line combination chemotherapy in the trials included in our systematic review is not maintained over subsequent lines of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies included in Amgen's NMA [n = 21, reported in 22 publications 28 [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] The reason for their exclusion was that they did not evaluate the effectiveness of the interventions in the RAS WT population. In addition to the abstracts for the OPUS 33 and CRYSTAL 34 trials included in the Amgen NMA, the Assessment Group identified the full publications.…”
Section: Comparison With the Assessment Group's Network-meta-analysismentioning
confidence: 99%
“…41-2 and pp. [87][88][89][90][91][92][93][94][95][96][97] and full results (including the results of the sensitivity analyses conducted) were reported (appendix 8, pp. 87-97).…”
Section: Network Meta-analysismentioning
confidence: 99%
“…If the pathological evaluation of the surgical specimen of patients reveals the luminal membrane expression of mesothelin in tumor cells in addition to lymph node metastasis, such patients should be treated with a more powerful first line adjuvant therapy to avoid the risk of further progression and metastasis of CRC [38,39]. Moreover, in case that an endoscopically resected specimen was evaluated as having "luminal membrane positive" of mesothelin, we may consider a much higher risk of lymph node metastasis; this might warrant our offering additional surgery and/or adjuvant chemotherapy to such patients, even if the endoscopic resection without adjuvant chemotherapy is a standard treatment for early stage CRC patients.…”
Section: Discussionmentioning
confidence: 99%